Revisiting relations between the British and the Malay establishments in Malaya - Mansor Majdin, Mohamad Firdaus; Zakariya, Hafiz (Journal of Humanities, Language, Culture & Business, 2017)
This paper examines the relations between the Malay establishments (Malay Sultans and Chiefs) and the British colonial government in Malaya from 19th to early 20th centuries. It reassesses the relations between both parties with regard to the socio-economic and political conditions in Malaya during the period under review. It is well known fact that the British authority required the support and cooperation of the Malay establishments in order to please the local communities and to give binding force upon any policies on Malaya. The paper also contends that the Malay Establishments as they were soon absorbed into the Western-style of administration of the states, depending on the British authority for their survival at the expense of steady progress of non-Malays in the fields of education, economy and administrative affairs. Therefore, the British, through their tactful and pragmatic approach, to certain extent, tied the Malay establishments within the orbit of the administration of state’s affairs as they proved to be a connecting point between the colonial government and the general masses. Such alliance was an important step towards general harmony and stability of the country especially against the arising national awareness within and outside the region.